How should we define a 'good' outcome from encephalitis A systematic review of the range of outcome measures used in the long-term follow-up of patients with encephalitis. Issue 2 (2022) - Tooren, Harriet Van Den; Easton, Ava; Hooper, Cory
No abstract available